The Influence Of Using Clubhouse Application On Fulfilling Information Needs Of Movies For Clubhouse Indonesia Community - Sitarani Andi Renasya; Pradipta Dirgantara (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
In the digital era people are constantly looking for information and how their needs of information can be fulfilled. The digital era provides various conveniences for its users, such as social media which allows individuals to communicate in ways that were previously unimaginable. This research was aimed to find out how big is the influence of using Clubhouse Application on fulfilling information needs of movies towards Clubhouse Indonesia Community. This research used 4C Components by Chris Heuer and four categories of predicted information needs by Guha. This research uses quantitative method by distributing questionnaires to 100 respondents through online media determined through nonprobability sampling. The population in this study is the member of Clubhouse Indonesia community. The analytical technique used in this research are descriptive analysis and simple linear regression analysis. The member of Clubhouse Indonesia community was the researcher’s sample for this study. The results of this study shows that the Clubhouse Application (X) has a positive and significant effect on the Information Needs (Y). Based on the results of the coefficient of determination, the results obtained that Yulia's Youtube channel Baltschun contributed 51.2% to the film's information needs, and the remaining 48.8% is the contribution of the influence of other variables not examined in this study. Keywords: Communication, Clubhouse, Information Needs, Movies